2016
DOI: 10.7717/peerj.2384
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the climatic tolerance and postglacial range changes of the most primitive orchids (Apostasioideae) within Sundaland, Wallacea and Sahul

Abstract: The location of possible glacial refugia of six Apostasioideae representatives is estimated based on ecological niche modeling analysis. The distribution of their suitable niches during the last glacial maximum (LGM) is compared with their current potential and documented geographical ranges. The climatic factors limiting the studied species occurrences are evaluated and the niche overlap between the studied orchids is assessed and discussed. The predicted niche occupancy profiles and reconstruction of ancestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(61 reference statements)
1
6
0
Order By: Relevance
“… Jersáková et al (2013) reported a variable genome size between Apostasia and Neuwiedia , with a nearly 16-fold range. Kolanowska et al (2016) assessed the evolution of cold tolerance among Apostasioideae species and proposed that their distribution was affected by climatic change. More recently, the genome sequence of Apostasia odorata has been sequenced ( Lin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… Jersáková et al (2013) reported a variable genome size between Apostasia and Neuwiedia , with a nearly 16-fold range. Kolanowska et al (2016) assessed the evolution of cold tolerance among Apostasioideae species and proposed that their distribution was affected by climatic change. More recently, the genome sequence of Apostasia odorata has been sequenced ( Lin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study reveal that climatic niche diversification did not significantly influence the speciation of the Neotropical angrecoid orchids. This is the third study showing that PNC in Orchidaceae is very high ( Kolanowska & Szlachetko, 2014 ; Kolanowska et al, 2016 ) and that their diversity cannot be explained by niche differentiation. Our results confirm Wiens’s assumption about the low effect of niche modification in speciation.…”
Section: Discussionmentioning
confidence: 76%
“…15,000,000 generations were performed in two runs, discarding the first 25% as the burning in fraction and sampling every 1,000th tree. To estimate node ages function chronos in package “ape” was used as described previously ( Kolanowska et al, 2016 ). Lambda was set to 20 and ages were estimated using a semi-parametric method based on penalized likelihood where branch lengths indicate mean numbers of substitutions ( Sanderson, 2002 ; Paradis, Claude & Strimmer, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolanowska 2013b, 2015. Recently, first estimates of phylogenetic niche conservatism and evolution of climatic tolerances within Apostasioideae were published (Kolanowska et al 2016).…”
mentioning
confidence: 99%